Question:২২.সমাধান কর: `2^x + 2^(1 - x) = 3`
Answer সমাধান: `2^x + 2^(1 - x) = 3` বা, `2^x + (2^1)/(2^x) = 3` বা, `a + 2/a = 3` [ `2^x = a` ধরে ] বা, `(a^2 + 2)/a = 3` বা, `a^2 + 2 = 3a` বা, `a^2 - 3a + 2 = 0` বা, `a^2 - 2a - a + 2 = 0` বা, `a(a - 2) - 1(a - 2) = 0` বা, `(a - 2)(a - 1)= 0` হয়, `a - 2 = 0` অথবা, `a - 1 = 0` বা, `a = 2` বা, `a = 1` বা, `2^x = 2^1` বা, `2^x = 2^0` `:. x = 1` `:. x = 0`; [ `a > 0, a != 1` শর্তে `a^x = a^y` হলে `x = y` ] `:.` নির্ণেয় সমাধান, `x = 0, 1`
+ Report
২২.shomadhan karo: `2^x + 2^(1 - x) = 3`